P4HA1, a Prognostic Biomarker that Correlates With Immune Infiltrates in Lung Adenocarcinoma and Pan-Cancer - Zhao, Qi; Liu, Junfeng (Frontiers in Cell and Developmental Biology, 2021)
Background: Prolyl 4-hydroxylase, alpha polypeptide I (P4HA1) is key enzyme in collagen synthesis composed of two identical alpha subunits and two beta subunits. However, the immunomodulatory role of P4HA1 in tumor immune microenvironment (TIME) of lung adenocarcinoma (LUAD) and pan-cancer still remains unclear. Methods: The expression, clinical features, mutation, DNA methylation, copy number alteration and prognostic value of P4HA1 in pan-cancer were evaluated using The Cancer Genome Atlas and Genotype-Tissue Expression data. Pathway enrichment analysis of P4HA1 was performed using the R package “clusterProfiler.” The correlation between immune cell infiltration level and P4HA1 expression was analyzed using three sources of immune cell infiltration data, including the ImmuCellAI database, TIMER2 database and a published work. Results: P4HA1 was substantially overexpressed in LUAD and other cancer types. High P4HA1 expression predicted poor survival in patients with LUAD. We also found that P4HA1 expression was positively associated with the infiltration levels of immunosuppressive cells, such as tumor-associated macrophages, cancer-associated fibroblasts, nTregs, and iTregs, and negatively correlated with CD8+ T and NK cells in pan-cancer, including LUAD. Conclusions: Our results revealed that P4HA1 is a potential prognostic biomarker in LUAD and pan-cancer. An elevated P4HA1 expression indicates an immunosuppressive microenvironment.